Kebenaran tentang menyampaikan maksud anda / Lonnie Pacelli ; penerjemah Fitria Liza ; editor Daniel P Purba, Yati Sumiharti - Pacelli, Lonnie; Lisa, Fitria Purba Daniel P Sumiharti, Daniel (2006)
XV, 258 18 cm